Analisis Hedonisme Iklan M-Banking BRImo di Televisi Amanda Rawles - Mutimmah, Nihayatul (LANCAH: Jurnal Inovasi dan Tren, 2024)
In this digital era, every company or producer in making advertisements has to have more creative advertising innovations so that the product message conveyed effectively and efficiently reaches all levels of society. This research is to analyze the creative message strategy and message appeal in the Amanda Rawles edition of the BRImo advertisement on television with an emphasis on the element of hedonism. The object of this research is the "easy and versatile" edition of the BRImo advertisement which will be broadcast on television in 2024. The research method used is semiotic analysis to find signs and meanings in the element of hedonism in the advertisement. The analysis results show that the BRImo advertisement displays a message with a creative strategy using the famous character Amanda Rawles and raises the theme of a hedonistic lifestyle. This aims to attract consumer attention. The Amanda Rawles edition of the BRImo advertisement conveys a message to consumers with a creative strategy of featuring famous figures and the concept of hedonism to appeal to the message.